Answer:
[tex]x-2y+1=0[/tex]
Step-by-step explanation:
We are given the following information in the question:
[tex]y = \sqrt{x}[/tex]
Differentiating y with respect to x:
[tex]\displaystyle\frac{dy}{dx} = \frac{1}{2\sqrtx}[/tex]
At x = 1
[tex] \displaystyle\frac{dy}{dx}\Bigr|_{\substack{x=1} }= \frac{1}{2\sqrt{1}}=\frac{1}{2}[/tex]
[tex]y(1) = \sqrt{1} = 1[/tex]
Equation of tangent:
[tex](y-y_0) = \displaystyle\frac{dy}{dx}(x-x_0)[/tex]
Putting the values:
[tex](y-y(1)) = \displaystyle\frac{dy}{dx}\Bigr|_{\substack{x=1} }(x-1)\\\\y - 1= \frac{1}{2}(x-1)\\2y -2 = x - 1\\x-2y+1=0[/tex]
The above equations are the required equation of the tangent.